Dichroic spin–valley photocurrent in monolayer molybdenum disulphide - Eginligil, Mustafa; Cao, Bingchen; Wang, Zilong; Shen, Xiaonan; Cong, Chunxiao; Shang, Jingzhi; Soci, Cesare; Yu, Ting (Nature communications, 2015)
The aim of valleytronics is to exploit confinement of charge carriers in local valleys of the energy bands of semiconductors as an additional degree of freedom in optoelectronic devices. Thanks to strong direct excitonic transitions in spin-coupled K valleys, monolayer molybdenum disulphide is a rapidly emerging valleytronic material, with high valley polarization in photoluminescence. Here we elucidate the excitonic physics of this material by light helicity-dependent photocurrent studies of phototransistors. We demonstrate that large photocurrent dichroism (up to 60%) can also be achieved in high-quality molybdenum disulphide monolayers grown by chemical vapour deposition, due to the circular photogalvanic effect on resonant excitations. This opens up new opportunities for valleytonic applications in which selective control of spin–valley-coupled photocurrents can be used to implement polarization-sensitive light-detection schemes or integrated spintronic devices, as well as biochemical sensors operating at visible frequencies. Valleytronic materials allow for band structure minima to be exploited in electronic transport devices in addition to charge and spin. Here, the authors demonstrate selective control of spin–valley-coupled photocurrents via circularly polarized light in molybdenum disulphide grown by chemical vapour deposition.